Albendazole negatively regulates keratinocyte proliferation. Issue 7 (17th April 2020) - Di Fusco, Davide; Stolfi, Carmine; Di Grazia, Antonio; Dinallo, Vincenzo; Laudisi, Federica; Marafini, Irene; Colantoni, Alfredo; Monteleone, Ivan; Monteleone, Giovanni
Abstract: Background: Increased keratinocyte proliferation occurs in the skin of psoriatic patients and is supposed to play a role in the pathogenesis of this disorder. Compounds interfering with keratinocyte proliferation could be useful in the management of psoriatic patients. Aim: To investigate whether albendazole, an anti-helmintic drug that regulates epithelial cell function in various systems, inhibits keratinocyte proliferation in models of psoriasis. Methods: Aldara-treated mice received daily topical application of albendazole. Keratinocyte proliferation and keratin (K) 6 and K16 expression were evaluated by immunohistochemistry and Western blotting and inflammatory cells/mediators were analysed by immunohistochemistry and real-time PCR. In human keratinocytes (HEKa and HaCaT) treated with albendazole, cell cycle and proliferation, keratins and cell cycle-associated factors were evaluated by flow cytometry, colorimetric assay and Western blotting respectively. Results: Aldara-treated mice given albendazole exhibited reduced epidermal thickness, decreased number of proliferating keratinocytes and K6/K16 expression. Reduction of CD3- and Ly6G-positive cells in the skin of albendazole-treated mice associated with inhibition of IL-6, TNF-α, IL-1β, IL-17A, IL-36, CCL17, CXCL1, CXCL2 and CXCL5 expression. Treatment of keratinocytes with albendazole reduced K6/K16 expression and reversibly inhibited cell growth by promoting accumulation of cells in S-phase. This phenomenon was accompanied by down-regulation of CDC25A, a phosphatase regulating progression of cell cycle through S-phase, and PKR-dependent hyper-phosphorylation of eIF2α, an inhibitor of CDC25 translation. In Aldara-treated mice, albendazole activated PKR, enhanced eIF2α phosphorylation and reduced CDC25A expression. Conclusions: Data show that albendazole inhibits keratinocyte proliferation and exerts therapeutic effect in a murine model of psoriasis.